2009
DOI: 10.1080/17451590902771342
|View full text |Cite
|
Sign up to set email alerts
|

Use of plants in healthcare: a traditional ethno-medicinal practice in rural areas of southeastern Bangladesh

Abstract: This study considered traditional ethno-medicinal practices of rural people of Feni district, Bangladesh, focusing on their utilization of medicinal plants and associated indigenous knowledge. Ninety households were interviewed using a semistructured questionnaire. Plant resources are used to treat 26 different ailments ranging from simple cuts to diabetes. In total, 46 medicinal plants are as used, of which a third are trees. Homesteads are the primary source and few medicinal plants are cultivated. Abovegrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 19 publications
4
39
0
1
Order By: Relevance
“…These medicinal plants include trees (34%), shrubs (32%), herbs (23%) and creepers (11%). In general, trees are the commonest medicinal plants in rural Bangladesh -as evident from several studies (e.g., Miah & Chowdhury 2003;Mukul et al 2007;Chowdhury et al 2009a). As rule, protected areas have a rich floral diversity, and in Rema-Kalenga Wildlife Sanctuary a total of 606 plant species were recorded during the period 1998-2000 in a floristic survey (Uddin 2001 , Mujib Nature Reserve of Jordan (Hudaib et al 2008), Satchari National Park of Bangladesh (Mukul et al 2007) and Velliangiri holy hills of India (Ragupathy et al 2007), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These medicinal plants include trees (34%), shrubs (32%), herbs (23%) and creepers (11%). In general, trees are the commonest medicinal plants in rural Bangladesh -as evident from several studies (e.g., Miah & Chowdhury 2003;Mukul et al 2007;Chowdhury et al 2009a). As rule, protected areas have a rich floral diversity, and in Rema-Kalenga Wildlife Sanctuary a total of 606 plant species were recorded during the period 1998-2000 in a floristic survey (Uddin 2001 , Mujib Nature Reserve of Jordan (Hudaib et al 2008), Satchari National Park of Bangladesh (Mukul et al 2007) and Velliangiri holy hills of India (Ragupathy et al 2007), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Among the medicinal plants, trees were the most frequent growth form (33.82%) followed by shrubs (26.47%), herbs (25%), creepers (11.70%) and palms (2.94%). In general, trees are the mostly used growth form of medicinal plants in rural Bangladesh as depicted in several studies (e.g., Miah and Chowdhury 2003;Mukul et al 2007;Chowdhury et al 2009) with a few exceptions as in Halim et al (2007) where they found that trees were used least among a religio-cultural group in southwestern part of the country. Other than Bangladesh, trees were found dominant medicinal plants among the Tharus, a forest dweller community of Nepal (Ghimire and Bastakoti 2009) unlike in Ethiopia where it was dominated by herbs (Dawit and Estifanos 1991;Yineger et al 2008).…”
Section: Medicinal Plants Recordedmentioning
confidence: 99%
“…Most people (36.67%) have agriculture as their major occupation. Feni is one of those 28 districts where literally no natural forests are located, rather marginal lands have become forested with the plantations of both indigenous and exotic tree species, where herbs and shrubs grow deliberately as understory (Chowdhury et al 2009). …”
Section: Figure 1 Location Map Of the Study Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] which has a strong historic evidence for its religious and therapeutic value [9] in the treatment of hiccups, dermatitis, athlete's foot, colitis, wound burns etc. [10] Decoction of flowers are very effective for cold conjunctivitis, mumps and eye sore. [11] Zingiber offcinale, commonly known as Ginger, belongs to Zingiberaceae family.…”
Section: Introductionmentioning
confidence: 99%